2017
DOI: 10.1016/j.sigpro.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Frequency estimation of multiple sinusoids with three sub-Nyquist channels

Abstract: Frequency estimation of multiple sinusoids is significant in both theory and application. In some application scenarios, only sub-Nyquist samples are available to estimate the frequencies. A conventional approach is to sample the signals at several lower rates. In this paper, we address frequency estimation of the signals in the time domain through undersampled data. We analyze the impact of undersampling and demonstrate that three sub-Nyquist channels are generally enough to estimate the frequencies provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…the range of f), the value of K' and K'' can be determined to solve f. This approach can be extended to multiple input signals and interpolation between FFT bins can be used to improve frequency estimation accuracy [20][21]. It should be pointed out that to avoid possible ambiguity when determining signal frequencies more sampling rates might be used and it has been shown that three ADC with different sampling rates are sufficient [9][10]. In this study, as the main purpose is to demonstrate the capability of a sub-Nyquist linear array, for simplicity, only two sampling rates are used in simulation.…”
Section: A Sub-nyquist Methods Using Adc With Different Sampling Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…the range of f), the value of K' and K'' can be determined to solve f. This approach can be extended to multiple input signals and interpolation between FFT bins can be used to improve frequency estimation accuracy [20][21]. It should be pointed out that to avoid possible ambiguity when determining signal frequencies more sampling rates might be used and it has been shown that three ADC with different sampling rates are sufficient [9][10]. In this study, as the main purpose is to demonstrate the capability of a sub-Nyquist linear array, for simplicity, only two sampling rates are used in simulation.…”
Section: A Sub-nyquist Methods Using Adc With Different Sampling Ratesmentioning
confidence: 99%
“…It has also been shown that a wideband receiver using multiple ADC with different sampling rates can cover several Nyquist zones [6][7][8][9][10]. Such a method is usually classified as a sub-Nyquist method.…”
Section: Introductionmentioning
confidence: 99%
“…Table 4 compares the computation complexity between the frequency-band division algorithm and robust CRT and closed-form CRT. rough careful analysis (17), (18), and (28) in [16], we find that the robust CRT method needs to calculate 4Γ 3…”
Section: Performance Comparison Between Frequency-bandmentioning
confidence: 99%
“…K is the number of channels) folding into the first Nyquist region and solve the frequency ambiguity in a short time. Usually, a fast Fourier transform (FFT) [16,17] algorithm is used to analyse the frequency to obtain high accuracy. However, the FFT algorithm has obvious shortcomings in processing time.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, their disadvantage is that they require the number of sinusoids to be known in advance, restricting their use in more general cases. One recent contribution that uses the MUSIC-based approach on the undersampled data is proposed in [15]. A numerical implementation of the ML estimator has been proposed in [16].…”
Section: Introductionmentioning
confidence: 99%